2019
DOI: 10.1098/rspb.2018.1916
|View full text |Cite
|
Sign up to set email alerts
|

A range-wide domino effect and resetting of the annual cycle in a migratory songbird

Abstract: Latitudinal differences in timing of breeding are well documented but how such differences carry over to influence timing of events in the annual cycle of migratory birds is not well understood. We examined geographical variation in timing of events throughout the year using light-level geolocator tracking data from 133 migratory tree swallows ( Tachycineta bicolor ) originating from 12 North American breeding populations. A swallow's breeding latitude influenced timing of breeding, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(84 citation statements)
references
References 44 publications
1
81
2
Order By: Relevance
“…Analyses of ring-recovery data have already suggested such flyway-scale differences in the timing of annual migration in, for example, white stork, Ciconia ciconia (Bairlein, 2001), but quantifying these differences for annual stages other than spring arrival often remains elusive with ring-recovery data. Earlier tracking studies of long-distance migrants have shown population-specific timing of annual migration routines, which are linked to spring phenology at various breeding latitudes Conklin, Battley, Potter, & Fox, 2010;Gow et al, 2019). Moreover, the northward progression of migrants in spring was found to be aligned with veg- .…”
Section: Seasonal Dynamicsmentioning
confidence: 81%
See 1 more Smart Citation
“…Analyses of ring-recovery data have already suggested such flyway-scale differences in the timing of annual migration in, for example, white stork, Ciconia ciconia (Bairlein, 2001), but quantifying these differences for annual stages other than spring arrival often remains elusive with ring-recovery data. Earlier tracking studies of long-distance migrants have shown population-specific timing of annual migration routines, which are linked to spring phenology at various breeding latitudes Conklin, Battley, Potter, & Fox, 2010;Gow et al, 2019). Moreover, the northward progression of migrants in spring was found to be aligned with veg- .…”
Section: Seasonal Dynamicsmentioning
confidence: 81%
“…Analyses of ring‐recovery data have already suggested such flyway‐scale differences in the timing of annual migration in, for example, white stork, Ciconia ciconia (Bairlein, ), but quantifying these differences for annual stages other than spring arrival often remains elusive with ring‐recovery data. Earlier tracking studies of long‐distance migrants have shown population‐specific timing of annual migration routines, which are linked to spring phenology at various breeding latitudes (Briedis et al, ; Conklin, Battley, Potter, & Fox, ; Gow et al, ). Moreover, the northward progression of migrants in spring was found to be aligned with vegetation phenology in the Nearctic–Neotropical migration system (La Sorte, Fink, Hochachka, Delong, & Kelling, ; Marra et al, ), where atmospheric and environmental conditions en route played an important role in shaping seasonal and flyway‐scale differences in migration strategies (La Sorte, et al, , ; La Sorte & Fink, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, environmental variables such as temperature or weather conditions can serve as cues for, or directly affect, migration traits (Ahola et al, 2004;Both et al, 2005;Marra et al, 2005;Knudsen et al, 2011;Haest et al, 2018). Seasonal carry-over effects can also influence phenology (Marra et al, 1998;Gow et al, 2019). Regarding the empirical evidence, we note that traits underlying migration speed are difficult to measure or may be inherently variable, small differences in these traits may be difficult to detect without large sample sizes, and departure day is not the same as the onset of predeparture fueling.…”
Section: Discussionmentioning
confidence: 95%
“…Migratory passerines (and near passerines) typically show several patterns of intraspecific co-variation in their breeding timing. These include protandry, which refers to the earlier onset of breeding activities in males than females (Newton, 2008;Morbey et al, 2012), the earlier arrival of adults than first-time breeders to breeding areas (Stewart et al, 2002), and later breeding timing at higher latitudes (Both and te Marvelde, 2007;Gow et al, 2019). Given sex-, age-, and latitude-specific breeding timing, differential migration schedules are expected, because migration is the life history phase immediately preceding breeding.…”
Section: Introductionmentioning
confidence: 99%
“…However, our results are consistent with those of Müller et al (), who have suggested that Scopoli's shearwater males leave the breeding areas earlier than females so they can arrive earlier in the subsequent reproductive season, in a kind of “domino effect” (Briedis et al, ). According to the “domino effect,” the timing of one phase of the annual cycle may affect the timing of the subsequent phase (Briedis et al, ; Gow et al, ), in this case, between postbreeding migration and arrival at the breeding colony for the subsequent reproductive season. Furthermore, although both sexes contribute equally to incubation and chick rearing (Hamer, Schreiber, & Burger, ), males tend to spend more time and energy defending the nests at the beginning of the breeding period, which could also explain their earlier arrival (Werner et al, ; Hedd et al, ).…”
Section: Discussionmentioning
confidence: 99%